Optimalisasi Penyuluhan Gizi Dan Program Kebugaran Ibu Hamil Untuk Mencegah Stunting Di Desa Gondangmanis : Implementasi Pengabdian Masyarakat - Latifa, Devi Indah; Susilo, Taufik Eko; Rahman, Farid; Naufal, Adnan Faris; Pristianto, Arif; Fatmarizka, Tiara (Jurnal Karya Nyata Pengabdian, 2025)
Stunting is one of the main health problems in Indonesia, caused by chronic lack of nutritional intake during the first 1,000 days of life, characterized by a child's height being shorter than children of the same age. Stunting prevention begins with ensuring that pregnant women get balanced nutritional intake and optimal physical activity during pregnancy. This study aims to optimize efforts to prevent stunting through nutritional counseling and fitness programs for pregnant women in Gondangmanis Village. The method used is a descriptive qualitative approach with a community service design. The activity was carried out in August 2024 involving 10 pregnant women as research subjects. The research stages include literature reviews, participatory observations, interviews, and documentation. The community service program includes two components, namely (1) counseling on balanced nutrition including demonstrations of nutritious food products (PMT) in the form of green bean corn pudding, and (2) fitness training for pregnant women. The results of the study showed that this program was successful in increasing the knowledge and awareness of pregnant women regarding the importance of balanced nutritional intake as well as the importance of physical activity for fitness in preventing stunting, although it has limitations in measuring the long-term impact on reducing stunting rates. The implementation of this program shows significant potential in Gondangmanis Village in efforts to prevent stunting through an educational approach.